2012
DOI: 10.1109/tdmr.2012.2192440
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-Induced Upsets in NAND Floating Gate Memories

Abstract: Abstract-We investigate atmospheric neutron effects on floating-gate cells in NAND Flash memory devices. Charge loss is shown to occur, particularly at the highest program levels, causing raw bit errors in multilevel cell NAND, but to an extent that does not challenge current mandatory error correction specifications. We discuss the physical mechanisms and analyze scaling trends, which show a rapid increase in sensitivity for decreasing feature size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Cellere et al [1][2] and Gerardin et al [3][4] have been the first to clearly state, using accelerated tests, that atmospheric neutron-induced soft error occurrence is possible in flash memories, although with extremely low probabilities at ground level. The exact physical mechanism(s) responsible of the floating-gate (FG) charge loss under natural radiation is(are) still an open issue; however Butt and Alam [5] recently proposed a complete physical model of single event upsets in floating gate memory cells that very satisfactory agrees with experimental data without any fitting parameter or phenomenological assumption.…”
Section: Introductionmentioning
confidence: 99%
“…Cellere et al [1][2] and Gerardin et al [3][4] have been the first to clearly state, using accelerated tests, that atmospheric neutron-induced soft error occurrence is possible in flash memories, although with extremely low probabilities at ground level. The exact physical mechanism(s) responsible of the floating-gate (FG) charge loss under natural radiation is(are) still an open issue; however Butt and Alam [5] recently proposed a complete physical model of single event upsets in floating gate memory cells that very satisfactory agrees with experimental data without any fitting parameter or phenomenological assumption.…”
Section: Introductionmentioning
confidence: 99%
“…We then showed that starting from a feature size of 50 nm, Multi Level Cell (MLC) Flash memories are sensitive to alpha particles, whereas SLC devices do not show any sensitivity down to a feature size of 34 nm. We also investigated atmospheric neutron effects [35]. Charge loss is shown to occur especially at the highest program levels, causing raw bit errors in MLC NAND.…”
Section: E Sensitivity Of Floating Gate Memories To Ionizing Radiatimentioning
confidence: 99%
“…On the other side, users are not required to implement any error correction codes in NOR Flash memories, making soft errors potentially more critical for this architecture. Recent reports indicate that the sensitivity to neutroninduced errors is growing as technology is scaling [3], due to the reduction in the number of carriers in the Floating Gate (FG), especially in state-of-the-art NAND Flash with MLC architecture, where only few hundred electrons separate two adjacent program levels. In these memories, the loss (or trapping) of just a few carriers due to ionizing radiation can be enough to upset a bit.…”
Section: Introductionmentioning
confidence: 99%